A Dynamic Growth Model with Equity for Guarantee Swap and Asymmetric Information. (28th February 2019) - Liu, Qi; Song, Dandan; Tang, Xiaolin
Abstract: We develop an endogenous dynamic growth model in which a financially constrained firm optimizes the entrance timing and financing structure in different information exposure scenes. An innovation financing tool called equity‐for‐guarantee swap is introduced to solve the dilemma of financing constraints. The productivity of the firm is a random variable following a two‐point distribution and its value can be observed in advance by the entrepreneur but not by the insurer. Our main goal is to fix the fair guarantee cost with asymmetry information and examine how the cost differs from the one under the same situation except with symmetric information. We solve a Nash equilibrium of the game between the entrepreneur and the insurer and specify the condition to determine whether a separating equilibrium or pooling one will be achieved. We find that at the separating equilibrium, the high‐profit firm will sacrifice a profit to send a signal for the purpose of separating itself from the low‐profit one by increasing the latter's mimicking cost. The pooling equilibrium occurs when the insurer can not distinguish the firm's type and therefore, the insurer demands the same guarantee cost for all firms.